BIOACTIVITY SCREENING OF SPONGES COLLECTED FROM BUNAKEN, MENADO BY Brine Shrimp Lethality Test AGAINST Artemia salina Leach - Astuti, Puji; Alam, Gemini; Wahyuono, Subagus (Indonesian Journal of Pharmacy, 2003)
Indonesia is one of the countries rich of natural resources. Sponges are marine invertebrates widely found in Indonesia and known to have various bioactive compounds with unique chemical structures. This study was aimed to screen potentially bioactive extracts of sponges collected from Bunaken and identify on their toxicity level against larva Artemia salina Leach. Samples were macerated using acetone followed by partition using chloroform and methanol. The extracts were prepared at the concentration of 100, 250, 500 and 1000 mg/ml and their toxicity was tested using Brine shrimp Lethality Test. LC50 (mg/ml) of the extracts was calculated using probit analysis. From the 4 extracts tested, all of them showed toxicity to larva Artemia. Chloroform extract of MD-02 was found to be the most toxic with the LC50 of 48.15 mg/ml and considered as a potential candidate for new drug research. Further characterization is still needed for the development in the future. This active sponge was then identified as Petrosia sp.Key words: sponges, Bunaken, bioactivity, Artemia salina Leach